Frequency and risk factors for the development of drug related problems among rheumatoid arthritis patients - Sujit Kumar Sah; Subramanian Ramaswamy; Madhan Ramesh (Elsevier, 2022)
Background: Rheumatoid arthritis (RA) patients are at high risk for development of drug related problems (DRPs) due to multiple drug use. This study aimed to estimate the frequency and risk factors for the development of drug related problems among RA patients in Indian setting. Methods: A prospective cohort study was carried out for twenty-two months in a tertiary care teaching hospital. Patients who met study eligibility criteria were randomised either into intervention or usual care group. All the patients' data were screened for the presence of DRPs. Identified DRPs were categorized into problems and their causes using Pharmaceutical Care Network Europe (PCNE V8.02) DRP Classification system. Clinical pharmacists proposed interventions to resolve DRPs in intervention group. Results: A total of 320 RA patients [Intervention group, n = 160 and usual care group, n = 160] were enrolled in this study. Overall, 463 DRPs were identified among 88.4% of patients, and frequency of DRPs was 1.6 per patient. Treatment safety (41.2%) and patient related factors (28.2%) was the most common category and cause of DRPs respectively. Advanced age and polypharmacy were the common risk factors identified for the development of DRPs. Conclusion: This study revealed DRPs are common among RA patients and those are related to the treatment safety and efficacy. Clinical pharmacists' provided interventions had significant impact on DRPs resolution among RA patients.